2020
DOI: 10.3390/ijms21020612
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Exhibits Inter-Individual Heterogeneity of TSPO and LAT1 Expression in Neoplastic and Parenchymal Cells

Abstract: Molecular imaging is essential for diagnosis and treatment planning for glioblastoma patients. Positron emission tomography (PET) with tracers for the detection of the solute carrier family 7 member 5 (SLC7A5; also known as the amino acid transporter light chain L system, LAT1) and for the mitochondrial translocator protein (TSPO) is successfully used to provide additional information on tumor volume and prognosis. The current approaches for TSPO-PET and the visualization of tracer ([18F] Fluoroethyltyrosine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 51 publications
2
39
0
1
Order By: Relevance
“…Cancer tissue hijack and alter metabolic pathways to increase amino acid transport for cell proliferation and survival 48 , 49 . Therefore, [ 18 F]FET has been utilized as an imaging biomarker targeting tumor cells and tumor progression 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Cancer tissue hijack and alter metabolic pathways to increase amino acid transport for cell proliferation and survival 48 , 49 . Therefore, [ 18 F]FET has been utilized as an imaging biomarker targeting tumor cells and tumor progression 50 , 51 .…”
Section: Discussionmentioning
confidence: 99%
“…TSPO expression correlates with states of inflammation in the CNS [ 27 ] and is commonly used as a marker of inflammation in positron emission tomography (PET) studies [ 82 ]. TSPO expression is also increased in the surrounding microenvironment in GBM, including microglia and macrophages [ 66 ]. Various analyses revealed that TSPO ligands can modulate inflammatory and immune responses [ 83 , 84 , 85 , 86 , 87 ].…”
Section: Role Of Tspo In Hallmarks Of Gbmmentioning
confidence: 99%
“…Interestingly, the upregulation of various pro-inflammatory genes [ 93 ] and M2 macrophage and neutrophilic gene signatures are significantly associated with the mesenchymal phenotype [ 42 ], which has the highest percentage of microglia, macrophage, and lymphocyte infiltration [ 94 ]. Given that TSPO expression is also associated with the mesenchymal subtype [ 66 ], it would be interesting to see if TSPO is involved in this regulation.…”
Section: Role Of Tspo In Hallmarks Of Gbmmentioning
confidence: 99%
See 2 more Smart Citations